Optimising Outpatient Pharmacy Staffing to Minimise Patients Queue Time using Discrete Event Simulation - Putri Amelia; Artya Lathifah; Muhammad Dliya'ul Haq; Christoph Lorenz Reimann; Yudi Setiawan (Journal of Information Systems Engineering and Business Intelligence, 2021)
Background: To remain relevant in the customer-oriented market, hospitals must pay attention to the quality of services and meet customers' expectations from admission to discharge stage. For an outpatient customer, pharmacy is the last unit visited before discharge. It is likely to influence patient satisfaction and reflect the quality of hospital's service. However, at certain hospitals, the waiting time is long. Resources need to be deployed strategically to reduce queue time.